2020
DOI: 10.1103/physrevx.10.021042
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Spin Liquid Phase of the Triangular Lattice Hubbard Model: A Density Matrix Renormalization Group Study

Abstract: Motivated by experimental studies that have found signatures of a quantum spin liquid phase in organic crystals whose structure is well described by the two-dimensional triangular lattice, we study the Hubbard model on this lattice at half filling using the infinite-system density matrix renormalization group (iDMRG) method. On infinite cylinders with finite circumference, we identify an intermediate phase between observed metallic behavior at low interaction strength and Mott insulating spin-ordered behavior … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
192
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(219 citation statements)
references
References 94 publications
27
192
0
Order By: Relevance
“…At half-filling, we find that the triangular lattice model without flux, = 0, becomes insulating for sufficiently strong interactions U > U Mott c 8.2 at T = 0.06in good agreement with previous numerical results [41][42][43]. In the following, we take U = 9.2, which corresponds to U 1.15 U Mott c and to the regime of moderately strong correlations at which a chiral spin liquid phase was found at half-filling in [43] (before the spins order for U > 10.6). A characteristic feature of the PG state is the opening of a partial energy gap in the spectral function A(k, ω) near the Fermi level, at certain regions in the Brillouin zone (BZ).…”
Section: Triangular Latticesupporting
confidence: 91%
“…At half-filling, we find that the triangular lattice model without flux, = 0, becomes insulating for sufficiently strong interactions U > U Mott c 8.2 at T = 0.06in good agreement with previous numerical results [41][42][43]. In the following, we take U = 9.2, which corresponds to U 1.15 U Mott c and to the regime of moderately strong correlations at which a chiral spin liquid phase was found at half-filling in [43] (before the spins order for U > 10.6). A characteristic feature of the PG state is the opening of a partial energy gap in the spectral function A(k, ω) near the Fermi level, at certain regions in the Brillouin zone (BZ).…”
Section: Triangular Latticesupporting
confidence: 91%
“…[16]) for a 'chiral spin liquid': a gapped state with semion topological order, but no antiferromagnetic order. More recently, a study [18] of the Hubbard model on the triangular lattice found evidence for the same chiral spin liquid even at J χ = 0. On the square lattice, Nielsen et al [19] studied the antiferromagnet with first (J 1 ) and second (J 2 ) neighbor exchange and a nonzero J χ , and found evidence for the chiral spin liquid at quite small values of J χ , but in relatively small system sizes.…”
Section: At Low Temperatures (T )mentioning
confidence: 89%
“…We estimate the hopping t between Wannier functions at neighboring triangular lattice sites to be ≈15 meV reflecting suppressed kinetic energy of the flat band electrons (Supplementary Table 4). In this context, the exotic electronic phases recently derived from the Hubbard model on triangular lattices, including spiral magnetic orders, unconventional superconductivity, and quantum or chiral spin liquids, might be relevant to the flat bands in kagome lattice [44][45][46] .…”
Section: Resultsmentioning
confidence: 99%